(untitled) (Journal of Applied Oral Science, 2021)
Pathological parameters have been indicated as tumor prognostic factors in oral carcinoma. Objective: The objective of this study was to investigate the impact of pathological parameters on prognosis of patients affected only by tongue and/or floor of the mouth squamous cell carcinoma (SCC). Methodology: In total, 380 patients treated in the Brazilian National Cancer Institute (INCA) from 1999 to 2006 were included. These patients underwent radical resection followed by neck dissection. The clinical and pathological characteristics were recorded. The Kaplan-Meier method and Cox proportional hazards model were used in survival analysis. Overall survival (OS), cancer-specific survival (CSS) and disease-free interval (DFI) were estimated. Cox residuals were evaluated using the R software version 3.5.2. Worst OS, CSS and DFI were observed in patients with tumors in advanced pathological stages (p<0.001), with the presence of perineural invasion (p<0.001) and vascular invasion (p=0.005). Results: Advanced pathological stage and the presence of a poorly differentiated tumor were independent prognostic factors for OS and CSS. However, advanced pathological stage and perineural invasion were independent predictors of a shorter OS, DFI and CSS. Conclusion: Pathological stage and perineural invasion were the most significant pathological variables in survival analysis in tongue and/or floor of the mouth SCC.